«ШӘРИЯР» ДӘСТАНЫН ОҚЫТЫЎДА ИНТЕРАКТИВ МЕТОДЛАРДАН ПАЙДАЛАНЫЎДЫҢ НӘТИЙЖЕЛИЛИГИ - Алламбергенов, Е.К. (FAN va JAMIYAT, 2020)
The article discusses the effectiveness of the use of innovative technologies, including interactive methods in the teaching of literature lessons. The researcher proves with convincing examples that such methods as "corners", "Sinkvein", "IREC" are effective methods of teaching the epic "Shariyar" in an interactive way.